Environmental sustainability of the water footprint in the Alto Piranhas sub-basin in the sertão paraibano, Brazil - Cândido, Luíza Lilandra Teixeira; Vieira, Allan Sarmento; Silva, Érika Lira da; Fernandes, Francisco Dinarte de Sousa; Sá Neto, José Abrantes de; Cândido, Raimundo Alves (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Advances in water management require knowledge of the availability and demand of water resources, as a subsidy to define priority actions that can conserve the proper use of water. The main objective of this article is to determine the water footprint in the Alto Piranhas sub-basin, located in the Sertão Paraíba, in 2015, and analyze its sustainability through operational scenarios. Based on this, studies were carried out with the water footprint methods in order to verify their efficiency and effectiveness in generating information on the amount of water consumed in the main water use sectors, as well as to analyze the sustainability of the studied sub-basin . The research is classified as exploratory and descriptive, since it involves bibliographic research, case study, data collection and also establish relations between variables so that it can reach the final result. The results of the research showed that the sub-basin is sustainable for the year of 2015, even though we have a very dry year and inefficient practices. However, when analyzed in the period from July to December the sub-basin presented high rates of scarcity and pollution, due to the reduction of natural flows. Therefore, the studies in the High Piranhas subbasin will subsidize the public manager in a precise decision-making and consequently promote the strengthening of the water resources management system that seeks sustainable governance.